Tropical Soda Apple Control: Sorting Through the Options - Jason A. Ferrell; Brent Sellers; Jeffrey J. Mullahey (EDIS)
SS-AGR-129, a 2-page fact sheet by J. A. Ferrell, B. Sellers, and J. J. Mullahey, presents a table describing the strengths and weaknesses of the new herbicide options that have arisen in the past three years for controlling tropical soda apple. Published by the UF Department of Agronomy, August 2006.